MODULE DEVELOPMENT OF GENDER HARMONY IN ISLAMIC EDUCATION PERSPECTIVE - Bagja Nugraha; Maemunah Sa'diyah; A. Rahmat Rosyadi (Universitas Muhammadiyah Surakarta, 2024)
This study aims to test the validity of the module on gender harmony which has an Islamic education perspective for students in high school. The method used is research and development level 1 formulated by Sugiyono. The development of the module begins with conducting a literature study on several sources related to the concept of gender and Islamic education. Then the modules that are being developed are tested on Islamic religious education experts, Indonesian language experts, and gender material experts. The results found that this module was considered very good with a validation score of 90,94% to be used in learning in high school. This module contains arguments, a communicative language style, and sufficient material to explain the concept of gender harmony to students.